Physico-Chemical Properties of Volcanic Soils under Different Perennial Plants from Upland Area of Mt. Merapi, Indonesia - Retno Kartikawati; Eko Hanudin; Benito Heru Purwanto (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2019)
Vegetation recovery is essential in land restoration after the eruption of Mount Merapi in 2010. Vegetation is a source of organic material that produces root exudate containing organic acids. These acids accelerate the dissolution process of volcanic material so that it affects the soil characteristics. This study was conducted to analyze the effect of four types of perennial plants on soil chemical and physical characteristics. The soil samples were taken on the area planted with cinnamon, albizia, bamboo, and acacia, at depths of 0 – 10 cm, 10 – 20 cm, 20 – 30 cm, 30 – 40 cm, and 40 – 50cm. The soil chemical analysis carried out included pH H2O, pH KCl, pH NaF, C-organic, Humic acid and Fulvic acid, cation exchange capacity, Ca, Mg, K, Na, available P, base saturation, and particle size distribution. The results show that pH H2O, pH KCl, C-organic, humic acid and fulvic acid, CEC, K, Na, Ca, Mg, available P, base saturation, and particle size distribution were significantly affected by vegetation type. Meanwhile, the pH of NaF was not significantly influenced by vegetation type. Cinnamon is a plant that gives the strongest influence in the improvement of soil chemical-physical properties compared to the other three types of vegetation. Therefore cinnamon is quite prospective plant to be developed for post-eruption land reclamation.